Védenje o vedenju - Kovačič, Matjaž (Organizacija znanja, 2008)
In his paper, the author presents the problem of how to scientifically define human behaviour through the relation between behaviour and the body on one side and social rules on the other. In scientific explanations of human behaviour, biological, physiological or medical understanding of the body is used, which further determines behavioural patterns either through sociological, cultural entities or entities of mind. These then have effect on the behaviour of an individual and indirectly also on his body. On the example of human behaviour, the paper makes us think about the relative status of scientific facts, the legitimacy of objectively proven statements, the methodology of natural sciences and the epistemological status of scientific "truths". In this, fundamental epistemological guiding principles are Cartesian scepticism and (cultural) relativism of knowledge. They both concur with the general framework of the sociology of knowledge, the main assumption of which is fictional or phantasmatic status of social reality. If the aforementioned statements are justified, this could lead to the re-definition of scientific classification of the knowledge on behaviour.
Keywords: človekovo vedenje; epistemologija; epistemology; filozofija znanosti; psihoanaliza; sociologija vednosti